Fatigue behaviour study on repaired aramid fiber/epoxy composites - Botelho, Edson Cocchieri [UNESP]; Mazur, Rogério Lago [UNESP]; Costa, Michelle Leali [UNESP]; Cândido, Geraldo Maurício; Rezende, Mirabel Cerqueira (FapUNIFESP (SciELO), 2009)
Aramid fiber reinforced polymer composites have been used in a wide variety of applications, such as aerospace, marine, sporting equipment and in the defense sector, due to their outstanding properties at low density. The most widely adopted procedure to investigate the repair of composites has been by repairing damages simulated in composite specimens. This work presents the structural repair influence on tensile and fatigue properties of a typical aramid fiber/epoxy composite used in the aerospace industry. According to this work, the aramid/epoxy composites with and without repair present tensile strength values of 618 and 680MPa, respectively, and tensile modulus of 26.5 and 30.1 GPa, respectively. Therefore, the fatigue results show that in loads higher than 170 MPa, both composites present a low life cycle (lower than 200,000 cycles) and the repaired aramid/epoxy composite presented low fatigue resistance in low and high cycle when compared with non-repaired composite. With these results, it is possible to observe a decrease of the measured mechanical properties of the repaired composites.
Keywords: Aramid/epoxy composite; Fatigue behavior; Mechanical behavior; Structural composites; Aramid fiber reinforced polymers; Composite specimens; Defense sectors; Fatigue behaviour; Fatigue resistance; High cycle; Low density; Structural repairs; Tensile and fatigue properties; Tensile moduli; Aerospace industry; Fiber reinforced plastics; Marine applications; Mechanical engineering; Mechanical properties; Repair; Tensile strength; Behavioral research